How do Professionals in Municipal Health and Welfare Relate to Bereaved Persons During the Acute Phase of a Drug-Related Death? A Qualitative Study - Hilde-Margit Løseth; Lillian B. Selseng; Kari Dyregrov; Sonja Mellingen (SAGE Publishing, 2022)
This study aims to broaden our knowledge of how professionals in municipal health and welfare relate to bereaved persons during the acute phase of a drug-related death. A reflexive thematic analysis was applied to six focus group interviews with 27 first responding personnel in Norway. The article describes the complexity and simultaneousness of the professional response. Three main themes were identified: (a) establishing contact, (b) diverse, supportive assistance, and (c) a complex helping context. The analysis showed that experiences from previous encounters and the deceased's illicit drug use affected many of the professionals' assessments, and implied an evaluation of the bereaved as not in need of emergency services or psychosocial follow-up. Professionals should be trained to understand drug-related death as a sudden and unnatural death, and to initiate immediate psychosocial crisis intervention. There is a need for further research on the perspective of professionals in the health and welfare services on the drivers and barriers to support (bereaved persons) during the acute phase.